# ﻿3/7 t+4=1/7 t-6

hala718 | Certified Educator

(3/7) t  + 4 = (1/7) t - 6

First let us multiply by 7:

7*(3/7)t + 4*7 = 7*(1/7)t - 6*7

==> 3 t + 28 = t - 42

Now group similar:

==> 3t - t = -42 - 28

==> 2t = -70

==> t = -70/2 = -35

==> t= -35

giorgiana1976 | Student

The answer depends on how the expression is written.

For instance, if the expression is:

﻿3t/7 + 4 = t/7 t - 6, so the ratios ﻿3/7 and 1/7 are the coefficients of t, we'll do in this way:

- we'll move all terms to one side:

﻿3t/7 + 4 - t/7 t + 6 = 0

We'll combine like terms:

2t/7 + 10 = 0

We'll multiply 10 and 0 by 7:

2t + 70 = 0

2t = -70

t = -35

I've calculated t because I've presumed that you want to solve the given linear equation.

The given expression could be written as:

﻿3/7 t + 4=1/7 t - 6

where the 2 ratios have as denominator, 7t.

If it's so, we'll move all terms to one side, we'll combine like terms and we'll get:

2/7t + 10 = 0

Now, we'll multiply 10 by 7t:

2 + 70t = 0

70t = -2

t = -2/70

t = -1/35

So, it's crucial to write correctly an equation!

neela | Student

To solve 3/7 t+4 = 1/7 t-6.

Solution:

3/7 t +4 = 1/7t -6 .

To collect t's on one side and numbers on the other side, subtract 1/7 t  +4 from both sides:

3/7 t +4 -(1/7 t +4)  = 1/7 t - 6  - (1/7t +4)

= 3/7 t -1/7 t = -6-4

(3/7-1/7)t = -10

2/7 t = -10

(2/7 t)/(2/7) = -10/(2/7) = -70/2 = -35

t = -35

krishna-agrawala | Student

Given:

(3/7)t + 4 = (1/7)t - 6

==> (3/7) t - (1/7)t = - 6 - 4

(2/7)t = - 10

Therefore:

t = - 10(7/2) = - 70/2 = - 35

t = -35